Msx2 Marks Spatially Restricted Populations of Mesenchymal Precursors. (October 2018) - Sakagami, N.; Matsushita, Y.; Syklawer-Howle, S.; Kronenberg, H.M.; Ono, W.; Ono, N.
Craniofacial development requires a set of patterning codes that define the identities of postmigratory mesenchymal cells in a region-specific manner, in which locally expressed morphogens, including fibroblast growth factors (FGFs) and bone morphogenetic proteins (BMPs), provide instructive cues. Msx2, a bona fide target of BMP signaling, is a transcription factor regulating Runx2 and osterix (Osx), whose mutations are associated with cranial deformities in humans. Here we show that Msx2 defines osteo-chondro precursor cells in specific regions of the craniofacial mesenchyme at the postmigratory stage, particularly in the mandibular process and the posterior cranial vault. Analysis of Msx2-creER mice revealed that early mesenchymal cells in proximity to the BMP4-expressing mesenchyme were marked upon tamoxifen injection, and their descendants contributed to diverse types of mesenchymal cells in the later stage, such as chondrocytes and perichondrial cells of the transient cartilage, as well as osteoblasts and suture mesenchymal cells. By contrast, Osx-creER marked osteoblast precursors at the later stage, and their descendants continued to become osteoblasts well into the postnatal stage. Therefore, Msx2 marks spatially restricted populations of mesenchymal precursor cells with diverse differentiation potential, suggesting that extrinsic molecular cues can dictate the nature of postmigratory mesenchymal cells in craniofacial development.